A [K,KL] sector based control design for nonlinear system - Sachan A.; Kamal S.; Singh D.; Xiong X. (My University, 2025)
A new approach for asymptotic stabilization of a general input-affine nonlinear system is presented. This relies upon the results of Matrosov's theorem to decompose the nth dimensional space. The construction of the [K,KL] sector for a nonlinear system is done with the suitable choice of control-Lyapunov function. The study of a nonlinear system is viewed from the perspective of comparison function for uniformity in solution. By means of designed sector, we design a switching controller which is well suited in the condition that shows its presence only outside of [K,KL] sector. Thus, it yields a stabilization scheme which saves the superfluous control termed as Lazy or Hands-Off control. Finally, we demonstrate the proposed approach which yields an asymptotically stable results for the simulation of an illustrative example. © 2018 ISA